Extraction of Anthocyanin Pigments from Red Onion (AlliumcepaL.) and Dyeing Woolen Fabrics - GUMRUKCU, GULSAH; USTUN OZGUR, MAHMURE; GULTEKIN, CENKKUT (Asian Journal of Chemistry, 2010)
Natural colours have attracted the attention of the entire world because of their non-hazardous nature. In present study, woolen fabrics were dyed with natural dyes derived from redonion (Alliumcepa L.) using various mordants by open bath dyeing technique. Natural dye (anthocyanins) was extracted from red-onion skins with acetic acid:ethanol:water (1:80:19, v/v/v) mixture solution. The amount of total anthocyanins was determined by using the derivative spectrophotometric method and found to be 13.5 mg/100 g for fresh onion skin and 5.2 g/100 g for dry onion skin. Dyeing processes were carried out according to pre-, together- and last-mordanting methods by using buffer solutions at the pH = 2-8 interval and for 1 h at 98-100 ºC. Some metal salts such as Al(OH)3, Cu(NO3)2, Fe(NO3)2, Zn(NO3)2, NiCl2, SnCl2, Pb(CH3COOH)2 were used as mordantation agents. In addition, various studies were carried out on the effect of mordant quantity and kind of mordant salt in dyeing. The colour changes were evaluated instrumentally with a colour difference meter. Colour differences in CIE L*a*b* units and gray scale classifications were reported. Dyeing conditions and other characteristics showed that mordant was more important than dye in predicting lightfastness of coloured textiles and good lightfastness which was between 2 and 4 values were obtained.